Intertextuality of Pupuh pangkur in Serat Wulangreh and the Implications for the Javanese Character Education - Veronika Unun Pratiwi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study seeks to examine Javanese traditional ethics and teachings, especially through an intertextual reading of Javanese Pupuh Pangkur chant text in Serat Wulang Reh. This study sought to learn more about the positive values that shape Javanese noble morals, as well as their representation and implementation in modern Javanese society, and their relationship to the idea of maintaining arts and culture in accordance with Javanese philosophy. The script writer Pupuh Pangkur wishes to remind the audience to be humble rather than arrogant. A person who exaggerates his strength or brags about his good deeds is considered arrogant, and such behavior is prohibited. An arrogant person also enjoys pointing out the flaws and shortcomings of others in public. People who exhibit these characteristics are despicable and should be avoided. People with bad personalities frequently commit acts such as taking away other people's rights, stealing, cheating, or corruption. Their primary goal in life is to make money and accumulate wealth. These people are influenced by worldly desires to pursue personal pleasures such as wasting money, drinking, having affairs with women, and so on.